Analisis kebebasan berpendapat (freedom of speech) dalam kaitannya dengan ujaran kebencian (hate speech) oleh mahasiswa di Kota Makassar - Irsyad Dhahri; Nurharsyah Khaer (Seminar Nasional LP2M UNM, 2019)
This study aims to analyse freedom of opinion in relation to the utterances of hatred by students of Universitas Negeri Makassar. This research uses descriptive qualitative method which is done by observing the subject and object of research based on the facts. The results of the study show that the opinions of students regarding freedom of opinion which are limited by the Hate Speech law are positive because generally students already know the Law regarding freedom of opinion and the Law on Hate Speech so that in their opinion be careful.